Bacterial cellulose membrane associated with red propolis as phytomodulator: Improved healing effects in experimental models of diabetes mellitus - Picolotto, Aline; Pergher, Dafiner; Pereira, Guilherme Pacheco; Machado, Keilla Gomes; Barud, Hernane da Silva; Roesch-Ely, Mariana; Gonzalez, Mario Henrique [UNESP]; Tasso, Leandro; Figueiredo, Jozi Godoy; Moura, Sidnei (Elsevier B.V., 2019)
Since early times, propolis has been used in folk medicine. The red propolis, collected in the northeast region of Brazil has been highlighted due to its popular use as an antimicrobial, with anti-inflammatory and healing properties, which are associated with its chemical composition. Here, we combine a bacterial membrane with red propolis to treat wounds of diabetic mice. This work aims to evaluate a biocurative from bacterial cellulose associated with red propolis in diabetic mice as wound healing model. Biocuratives from bacterial cellulose membrane and different extracts of red propolis were produced. The qualification and quantification of the presence of propolis chemical compounds in the membrane were investigated through high-resolution mass spectrometry (HRMS). Tests in vivo with biocuratives were performed on Swiss male diabetic mice induced by estroptozotocin. The animals were submitted to a surgical procedure and a single lesion was produced in the dorsal region, which was treated with the biocuratives. Macroscopic assessments were performed at 2, 7 and 14 postoperative days, and biopsies were collected on days 0, 7 and 14 for histological analysis, myeloperoxidase enzyme activity (MPO) and cytokines (TNF-alpha, IL-1 beta, and TGF-beta). Altogether, ten compounds were identified in membranes and five were further quantified. The ethyl acetate extract showed more red propolis markers, and the most prevalent compound was Formononetin with 4423.00-2907.00 mu g.g(-1). Macroscopic analyses demonstrated that the two groups treated with red propolis (GMEBT and GMEAE) showed significantly greater healing capabilities compared to the control groups (GS and GMS). An increase in leukocyte recruitment was observed, confirmed by the activity of the enzyme myeloperoxidase (MPO) in GMEBT and GMEAE groups. The levels of TNF-alpha were significantly higher in wounds stimulated with red propolis, as well as in TGF-beta (GMEBT and GMEAE) on day 7. This was different from the IL-1 beta levels that were higher in the control groups (GS and GMS). In summary, the biocuratives produced in this work were able to accelerate the wound healing process in a diabetic mouse model. In this way, the traditional knowledge of red propolis activity helped to create a biotechnological product, which can be used for diabetic wound healing purpose.
Keywords: Red; propolis; Diabetes mellitus; Wounds healing; Flavonoids